Heritage and Museums: Cultural Public Policies in Brazil (Cadernos de Sociomuseologia, 2014)
This paper appeared in class in the doctoral program Sociomuseology, Lusophone University of Humanities and Technologies. The approach of this article is questioning and plays an important role in understanding and expansion of the discussions about these issues in relation to what is proposed and what is implemented. Are recurring themes of Brazilian reality that demand a lot of attention, because they deal in the life of many people, especially the public employee money in these stocks. Key words: Public policies, Cultural Policies, Museums, Heritage.